Research directives toward deciphering adverse outcome pathways induced by environmental metallotoxins. (August 2016) - Sarigiannis, Dimosthenis A; Salifoglou, Athanasios
Graphical abstract: Highlights: Environmental metallotoxins pose a systemic health risk to humans. Research directives necessitate exposome perusal through systems biology approaches. Biophysical-biochemical and biology methods probe metallotoxin molecular interactions. Omics-bioinformatics generate profile, genotypic-phenotypic correlations and biomarkers. Adverse outcome assessment ushers in prevention, diagnosis and health therapeutics. Abstract : Environmental metallotoxins (Cd, Hg, Pb, As, Cr) influence profusely human health. Consequently, clear research directives are required to probe the complexity of risk and disease associations with exposure to metallotoxins. Systems biology approaches targeting the exposome provide efficient routes to organ-tissue profiling, while concurrently distinguishing physiology from deviating potential disease states. Sample processing and biophysical-biochemical methods in concert with metallotoxin speciation describe hybrid molecular interactions with extra/intracellular targets, establishing networks on normal physiology-aberrant functions at the cellular, tissue-organ and whole organism levels. Omics technologies, combined with bioinformatics, delineate emerging interactions, generating profiles, genotypic-phenotypic relationships, and biomarkers key to elucidating adverse outcomes on health. Collectively, the emerging exposome description provides tools expediting physiology-disease assessment and validation, further supporting preventive diagnostic-prognostic and potentially therapeutic technologies.